2012
DOI: 10.1073/pnas.1205977109
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen isotopes in tree rings are a good proxy for Amazon precipitation and El Niño-Southern Oscillation variability

Abstract: We present a unique proxy for the reconstruction of variation in precipitation over the Amazon: oxygen isotope ratios in annual rings in tropical cedar (Cedrela odorata). A century-long record from northern Bolivia shows that tree rings preserve the signal of oxygen isotopes in precipitation during the wet season, with weaker influences of temperature and vapor pressure. Tree ring δ 18 O correlates strongly with δ 18 O in precipitation from distant stations in the center and west of the basin, and with Andean … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

13
145
2
4

Year Published

2013
2013
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 175 publications
(187 citation statements)
references
References 56 publications
13
145
2
4
Order By: Relevance
“… 18 O studies on teak from India (Managave et al, 2010a;Managave et al, 2011) found both negative and positive correlations with the amount of rainy season rainfall at inter-and intra-annual scale. Studies in tropical regions of South-America have likewise reported negative correlation with the rainfall amount during rainy season (Ballantyne et al, 2010;Brienen et al, 2012), as have isotope studies in Southeast Asia (Sano et al, 2012;Xu et al, 2011;Zhu et al, 2012). However, none reported correlations with dry and rainy season rainfall as revealed here for Indonesian teak.…”
mentioning
confidence: 37%
See 1 more Smart Citation
“… 18 O studies on teak from India (Managave et al, 2010a;Managave et al, 2011) found both negative and positive correlations with the amount of rainy season rainfall at inter-and intra-annual scale. Studies in tropical regions of South-America have likewise reported negative correlation with the rainfall amount during rainy season (Ballantyne et al, 2010;Brienen et al, 2012), as have isotope studies in Southeast Asia (Sano et al, 2012;Xu et al, 2011;Zhu et al, 2012). However, none reported correlations with dry and rainy season rainfall as revealed here for Indonesian teak.…”
mentioning
confidence: 37%
“…Plant physiological effects like leaf water enrichment due to transpiration (Barbour, 2007;Helle and Schleser, 2004b;McCarroll and Loader, 2004;Roden et al, 2000) do not seem to be particularly pronounced in  18 O records from tropical tree rings (e.g. Brienen et al, 2012). Variation of …”
mentioning
confidence: 99%
“…Brienen et al (2012) reported that "inter-annual" variations in δ 18 O wc of Cedrela odorata trees sampled in northern Bolivia were correlated strongly with those of δ 18 O prec measured at considerably distant sites (>1000 km) in the Amazon, including Manaus. In the case of E. coriacea, however, the seasonal δ 18 O wc patterns of the trees in Manaus were not similar to those in the other two study areas (EC-JU, EC-AT; Fig.…”
mentioning
confidence: 99%
“…In tropical regions, oxygen isotope data from tree rings (δ 18 O TR ) are often more sensitive to precipitation than ring width (e.g., Brienen et al, 2012;Schollaen et al, 2013). δ 18 O TR data are primarily controlled by the isotopic composition of precipitation, i.e., the source water, and relative humidity (e.g., Barbour, 2007;McCarroll and Loader, 2004).…”
Section: Introductionmentioning
confidence: 99%